IMPROVING STUDENT LEARNING ACTIVITIES THROUGH THE DEMONSTRATION METHOD - Rizatrisna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was conducted due to the low level of student activities. The purpose of this research is to increase student activity in learning. One of the actions taken by the researcher was the application of the demonstration method. This research was a classroom action research conducted on grade I students of SDN 42 Mandau, totaling 23 students. Data were collected using observation sheets to observe teacher actions and student activities. The results showed that the demonstration method can increase learning activities of SDN 42 Mandau students, with teacher actions reaching 56% and student activities 59%, categorized as sufficient in the first cycle. In the second cycle, teacher actions increased to 79% and student activities to 80%, categorized as good. Based on the results, it can be concluded that the demonstration method can effectively increase PAI learning activities for grade I students at SDN 42 Mandau.